Guide for Development of Permanent Part-Time Employment Opportunities for Girls and Women - Berry, Jane.; Missouri Univ., Kansas City. School of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
Development of permanent part time employment is seen as a solution to employer needs and the changing life style of women; opportunities exist in banking, retail sales, education, and government agencies. Development of such positions will demand from employers and employment services the assessing of jobs for part time potential, publicizing work opportunities and labor supply, forming skill banks, and planning careers. Profiles of successful women who work part time illustrate the variety of opportunities; future projections indicate increased demand in the labor market as well as increasing availability of labor. Development of the supportive services of day care for children, vocational counseling, and communication centers must accompany increased employment opportunities. (Document includes a selected bibliography of books, government publications, conference proceedings, and pamphlets, and the appendix contains the questionnaires and survey instruments used.) (pt)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bibliographies; Day Care; Employment Projections; Employment Services; Guidance Centers; Publicize; Questionnaires; Employed Women; Employment Opportunities; Guidelines; Job Development; Part Time Employment